Unique equilibrium in a model of rule of law - Randolph Luca Bruno (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
This paper presents a model of Rule of Law in which a continuum of agents plays against the State for the appropriation of the economic assets of a stylised economy. The model shows how each agent can either challenge the State or acquiesce, with the latter having the choice of either protecting property rights or abandoning the economy to anarchy. Players' payoffs are affected by strategic complementarities, not only between State and agents but also among agents themselves. As a consequence of this, a Coordination Failure is generated. The solution of the game is given by two Pareto-ranked Nash equilibria emerging from the context. Introducing idiosyncratic information and sequential play generates a unique equilibrium, according to the global game approach. On the one hand, this model predicts that high uncertainty and sunk costs in law enforcement have a negative effect, pushing the economy towards a Pareto-dominated equilibrium. On the other hand, the high value given to the economy's assets (embedded social norms) has a positive influence, leading to a Pareto-dominant equilibrium.
Keywords: D81; C72; K42; 330; Rule of Law; Coordination Failure; Global Games; Rechtsstaat; Spieltheorie; Theorie; Gleichgewicht